Detailed investigation of the influence of preparation method on the conduction mechanism and dielectric properties of LiNbO3 compound - Guithi, K.; Sekrafi, H. E.; Ben Jazia Kharrat, A.; Khirouni, K.; Boujelben, W. (Indian journal of physics, 2025)
In this research, we investigate the structural, electrical, and dielectric properties of the LiNbO3 compound. Our sample was elaborated using two methods: solid–solid (sample S1) and sol–gel (sample S2). X-ray diffraction analysis with Rietveld refinement confirmed that both samples are single-phase and crystallize in the rhombohedral structure with the R3c space group.Theelectrical and dielectric properties of the LiNbO3 compound have been studied using the impedance spectroscopy technique. DC measurements revealed semiconducting behavior for the S1 sample across the entire temperature range investigated, except for a metallic character observed between 400 and 500 K. In contrast, the S2 sample exhibited metallic behavior only between 400 and 460 K. AC data analysis indicated that the conductivity σAC obeys the Jonscher power law. Nyquist plots, consistent with the Cole–Cole model, allowed us to propose an equivalent circuit that incorporates the contributions of electrodes, grains, and grain boundaries to the conduction process. Dielectric measurements illustrate that the dielectric relaxation is governed by the DC conduction process. Furthermore, the high permittivity values measured support the potential application of this compound in electronic devices. These findings demonstrate the reliability of our LiNbO3 compound for electronic device applications.